2015
DOI: 10.1002/chem.201500524
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerization‐Mediated Molecular Switching Between Six‐ and Seven‐Membered Rings Stabilized by Hydrogen Bonding

Abstract: 1,3,4,6-Tetraketones typically undergo keto-enol tautomerism forming bis-enols stabilized by intramolecular hydrogen bonding in two six-membered rings. However, 1,3,4,6-tetraketones derived from the terpene ketone camphor and norcamphor exist as isomers with two distinguishable modes of intramolecular hydrogen bonding, namely, the formation of six- or seven-membered rings. The structural requirements for this so far unknown behavior were investigated in detail by synthesis and comparison of structural analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The most important is that the highest energy barrier to overcome in the mentioned path has a value of 143.2 kJ/mol and it is related to the proton shift. That kind of barrier should be taken into account for the explanation of previous results in tautomerizable switches [51]. More detailed discussion is collected in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 95%
“…The most important is that the highest energy barrier to overcome in the mentioned path has a value of 143.2 kJ/mol and it is related to the proton shift. That kind of barrier should be taken into account for the explanation of previous results in tautomerizable switches [51]. More detailed discussion is collected in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 2, the 1 H -1 H COSY spectrum of (+)-1a suggested the presence of four isolated spin systems (HÀ C(8) to HÀ C(9), HÀ C (11) to HÀ C(15), H 2 À C(7') to H 2 À C(8'), HÀ C(10') to HÀ C(14')). In the HMBC spectrum, the correlations between HÀ C (16) and C(1)/C(2)/C(3), between HÀ C(18) and C(3)/C(5)/ C (17), between HÀ C(8) and C (10), as well as between HÀ C(9) and C(7)/C(11) indicated the presence of a 2,2,4-trimethylated-cinnamoyl-β-triketone unit (part 1 A, Figure 2). [14] Notably, the unusual downfield shifts of OHÀ C(7) (δ H 18.42), as well as the HMBC cross peaks between OHÀ C(7) and the five carbon signals at C(4)/ C(5)/C(6)/C(7)/C(8) indicated the keto-enol tautomeric equilibrium between C(7) and C(5).…”
Section: Resultsmentioning
confidence: 99%
“…[15] As shown in the HMBC experiment of (+)-1a, correlations between the enolic hydroxy signal at δ H 18.42 and C(4)/C(5)/C(6)/C(7)/C(8) were observed (Figure S34), indicated that the enolic hydroxy unit interconverted fast between C(5) and C(7) to form tautomers T1 ((E)À C(7)-enol form) and T2 (C(5)-enol form) through keto-enol tautomerism (Figure 4). [15][16][17] Moreover, the correlation signals between the enolic hydroxy proton and C(7)/C(8) are stronger than that with C(4)/C(5) (Figure S34), indicated that tautomer T1 predominated over tautomer T2. [15] Similar to (+)-1a, the minor isomer (+)-1b could be regarded as an equilibrium mixture of T3 (C(1)-enol form) and T4 ((Z)À C( 7)-enol form), and T4 was slightly more favorable (Figure S34).…”
Section: Resultsmentioning
confidence: 99%
“…Alkane- and arene-1,3,4,6-tetraketones were prepared using methods based on those described in the literature. , A series of bipyrazoles was synthesized through the condensation reaction of hydrazine hydrate and an alkane- or arene-1,3,4,6-tetraketone (2:1 ratio). D Bu 2 Al 3 Me 5 , D Ad 2 Al 3 Me 5 , D Pr 2 Al 3 Me 5 , D tolyl 2 Al 3 Me 5 , and D ph 2 Al 3 Me 5 were synthesized through the reaction of bipyrazole ligands and AlMe 3 (2:3 ratio).…”
Section: Results and Discussionmentioning
confidence: 99%